2020
DOI: 10.20408/jti.2020.004
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Volume and Performance of a regional Trauma Center in Korea: Initial 5-year analysis

Abstract: Purpose: We aimed to evaluate the trauma volume and performance indicators during the first 5-year period of operation in a single regional trauma center. methods: We analyzed prospectively collected data from the Korean Trauma Data Bank for a single regional trauma center between January 2014 and December 2018. More than 250 variables were analyzed. We calculated the predicted survival rates using the trauma and injury severity score (TRISS) method. results: In total, there were 16,103 trauma admissions durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Numerous variables, including the demographics, pre-hospital and in-hospital information, time factors, clinical characteristics, vital signs, trauma scores, and final outcome information, were recorded. Therefore, the quantity and quality of the KTDB data were satisfactory 25 .…”
Section: Discussionmentioning
confidence: 97%
“…Numerous variables, including the demographics, pre-hospital and in-hospital information, time factors, clinical characteristics, vital signs, trauma scores, and final outcome information, were recorded. Therefore, the quantity and quality of the KTDB data were satisfactory 25 .…”
Section: Discussionmentioning
confidence: 97%
“…Fortunately, several recent reports, including this one, have demonstrated that several Korean regional trauma centers have been successfully established and have contributed to the improvement of local trauma performance. 3 5 Nevertheless, differences exist in the quality and extent of trauma care at the 15 regional trauma centers that have officially been operating. According to Jung et al, 5 initial trauma centers have reported good outcomes, but trauma centers that have just commenced operating or have yet to open face difficulties in securing manpower and establishing relevant systems.…”
Section: Discussionmentioning
confidence: 99%
“…There have been recent reports on outcomes resulting from performance improvements in trauma care in institutions that opened earlier and have been operating trauma centers for more than 5 years. 3 4 The most recently published national survey revealed that regional trauma centers had lower PTDRs. 5 Based on these results, it is projected that national trauma outcomes can be improved if the operation of these trauma centers is further established and a system promoting the concentration of severe trauma patients in regional trauma centers is supported.…”
Section: Introductionmentioning
confidence: 99%
“…A higher prevalence of trauma has been reported in younger people, affecting twice as many men as women [ 2 3 4 ]. The preventable trauma death rate in South Korea is reportedly higher than that in other developed countries, despite declining from 40.5% in 1997 to 39.6% in 2003, 35.3% in 2009, and 30.5% in 2015 [ 5 6 7 ]. Trauma can be prevented through proactive interventions addressing environmental, equipment, behavioral, and individual risk factors in the public domain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%